Effect of Clove Oil on the Storage Quality of Aerobically Packaged Fiber Enriched Chevon Cutlets - Singh, Pramod Kumar; Kumar, Sunil; Bhatt, Z.F; Kumar, Pavan (Journal of Meat Science, 2014)
A study was conducted to evaluate the potential of clove oil as a natural preservative in muscle foods by assessing its effect on the storage quality of fiber-enriched chevon cutlets. Chevon cutlets containing optimum level of the barley flour (4 percent) treated with and without clove oil (100 ppm) were aerobically packaged in low density polyethylene pouches along with control (chevon cutlets without barley flour and without clove oil - T1, chevon cutlets with barley flour and without clove oil -T2, chevon cutlets without barley flour and with clove oil - T3 and chevon cutlets with barley flour and with clove oil - T4) and evaluated for storage quality for 15 days under refrigerated conditions (4±1oC). The products were analyzed for various physico-chemical, microbiological and sensory parameters. TBARS value (mg malonaldehyde/kg), total plate count (log CFU/gm), psychrophillic count (log CFU/gm) and yeast and mould count (log CFU/gm) showed significant (P
Keywords: Cutlets; Chevon; Barley; Clove oil; Refrigerated storage